Single-cell insights: Mosquito Toll activation enhances granulocyte differentiation and immune surveillance via Notch suppression - Banhisikha Saha; Colton M. McNinch; Stephanie Serafim De Carvalho; Ana Beatriz Barletta Ferreira; Carolina Barillas-Mury (Proceedings of the National Academy of Sciences, 2026)
Activation of the Toll, Immunodeficiency (IMD), Jun-kinase (JNK), and Signal Transducer and Activator of Transcription (STAT) innate immune signaling pathways limits Plasmodium infection in Anopheles gambiae . Hemocytes (mosquito immune cells) restrict malaria transmission by eliminating Plasmodium parasites through complement-mediated lysis and phagocytosis. However, the mechanisms underlying mosquito hemocyte lineage determination and maturation remain poorly understood. Here, we used single-cell transcriptomics to investigate how these immune signaling pathways regulate hemocyte differentiation and function. Analysis of 37,529 hemocytes revealed oenocytoid and granulocyte subpopulations not previously described that express specific molecular markers, as well as the expansion of selective subpopulations by different signaling pathways. Toll and JNK activation trigger terminal differentiation of granulocytes (phagocytic cells) with a dramatic increase in megacytes and reduce oenocytoids by transcriptionally suppressing Notch signaling. Toll activation strongly affects gene expression in most hemocyte clusters, whereas STAT and IMD activation impact only specific clusters. Moreover, Toll activation induces the expression of extracellular matrix-interacting genes in megacytes, enhancing midgut immune surveillance. Collectively, these findings uncover how immune signaling modulates hemocyte differentiation and function in a medically relevant mosquito species, providing insights into the mechanism by which hemocytes hinder Plasmodium infection.